DIVERSIFICATION WITH THE OPTION-TO-ABANDON: AN INTEGRATED VALUATION MODEL - Mello-e-Souza, Carlos A. De (Revista Universo Contábil, 2015)
A model that recognizes the possibility of total shareholder loss in the aftermath of bankruptcy reveals simultaneously the stock price effects of diversification and of the option to abandon assets to creditors. In essence the model integrates security pricing behavior predicted by the CAPM and by the OPM in a single formula. Results have implications for the valuation of equity and debt securities of firms in distress and of options when underlying cash flows are correlated with the market. The analysis suggests why models that consider only diversification or the option-to-abandon sometimes fail to track the behavior of actual returns.